Antimicrobial Resistance in Outpatient Escherichia coli Urinary Isolates in Dakar, Senegal - Jean-Marie Sire,1 Pierre Nabeth (The Journal of Infection in Developing Countries, 2007)
Background: Data regarding the evolution of antimicrobial resistance are needed to suggest appropriate empirical treatment of urinary tract infections (UTI) in developing countries. To assess the antimicrobial susceptibility of Escherichia coli, thepredominant pathogen in community-acquired UTI, a prospective multicenter study was carried out in Dakar, Senegal.Methodology: From February 2004 to October 2006, 1010 non-duplicate E. coli strains were collected from four centres. Antimicrobial susceptibility testing was performed using disk diffusion method according to the recommendations of the CA-SFM(2004).Results: Most of the isolates were resistant to amoxicillin (73.1%), amoxicillin-clavulanic acid (67.5%), cephalothin (55.8%), and trimethoprim/sulfamethoxazole (68.1%). Extended spectrum beta-lactamase was detected in 38 strains. The overall resistance rates to nalidixic acid, norfloxacin and ciprofloxacin were 23.9%, 16.4% and 15.5%, respectively. Most of the strains were susceptible to gentamicin, nitrofurantoin and fosfomycin (respective susceptibility rates, 93.8%, 89.9%, and 99.3%). During this period, a significant decrease in sensitivity was observed for cephalothin, fluoroquinolones and trimethoprim/sulfamethoxazole (p<0.001).Conclusions: These data suggest that trimethoprim/sulfamethoxazole may no longer be used as empirical treatment for community-acquired UTI in Dakar. In order to preserve the activity of fluoroquinolones for future years, alternatives such asfosfomycin or nitrofurantoin should be considered.